ASOTHYRIAN IMAGERY AND PHILOSOPHY IN THE ANCIENT EAST THE EMERGENCE OF KNOWLEDGE - Davronova Umida Akram qizi; Mustafoyev Jafar Shomirzayevich (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Abstract: This article discusses the early stages of the philosophy of the Ancient East, its influence on the minds and lives of the inhabitants of this land, the role of philosophy in the life of the Ancient East.